Dynamics of TCP traffic over ATM networks. - Romanow, Allyn (Computer communication review.)
We investigate the performance of TCP connections over ATM networks without ATM-level congestion control, and compare it to the performance of TCP over packet-based networks. For simulations of congested networks, the effective throughput of TCP over ATM can be quite low when cells are dropped at the congested ATM switch. The low throughput is due to wasted bandwidth as the congested link transmits cells from ?corrupted? packets, i.e., packets in which at least one cell is dropped by the switch. This fragmentation effect can be corrected and high throughput can be achieved if the switch drops whole packets prior to buffer overflow; we call this strategy Early Packet Discard. We also discuss general issues of congestion avoidance for best-effort traffic in ATM networks.